2006
DOI: 10.1007/s00192-005-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Perineal endometriosis in episiotomy scar with anal sphincter involvement: report of two cases and review of the literature

Abstract: Perineal endometriosis with anal sphincter involvement is a rare occurrence with only nine cases reported so far. Two such cases are presented, and the literature is reviewed. In presented cases, diagnosis was suspected at clinical exam. Anal manometry was performed in both cases and endoanal ultrasound in one case. Wide surgical excision of endometriotic mass together with part of external anal sphincter was carried out in both cases. The procedure was followed by anal sphincter reconstruction in an "overlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Barisic et al advocated wide excision of the nodule with primary sphincteroplasty, in order to achieve good healing with preservation of fecal continence in cases of scar endometrioma due to episiotomy involving the anal sphincter. 39 Kokuba et al found that a technique involving two semicircular defatted flaps was efficient for creating a neo-umbilicus after removing umbilical scar endometrioma. 40 The curative surgery should preferentially be performed some days before the menstrual period, thus avoiding an inflammatory reaction and making tissue removal easier.…”
Section: Discussionmentioning
confidence: 99%
“…Barisic et al advocated wide excision of the nodule with primary sphincteroplasty, in order to achieve good healing with preservation of fecal continence in cases of scar endometrioma due to episiotomy involving the anal sphincter. 39 Kokuba et al found that a technique involving two semicircular defatted flaps was efficient for creating a neo-umbilicus after removing umbilical scar endometrioma. 40 The curative surgery should preferentially be performed some days before the menstrual period, thus avoiding an inflammatory reaction and making tissue removal easier.…”
Section: Discussionmentioning
confidence: 99%
“…Wide excision of the endometrial tissues with a good healthy margin is important even if this necessitates primary sphincteroplasty when the anal sphincter is involved. It has the best chance of cure and is recommended in all cases where such an excision does not compromise function of adjacent structures and organs (Barisic et al, 2006).…”
Section: Surgical Managementmentioning
confidence: 99%
“…This may necessitate primary sphincteroplasty to lesson the risk of fecal incontinence. A PubMed search showed only 13 cases of perineal endometriosis with anal sphincter involvement in eleven different case reports since 1957 (Bacher et al, 1999;Barisic et al, 2006;Beischer et al, 1966;Dougherty & Hull, 2000;Gordon et al, 1976;Hambrick et al, 1979;Kanellos et al, 2001;Martı´nez et al, 2002;Prince & Abrams, 1957;Sayfan et al, 1991;Toyonaga, 2006). In the 13 cases of PEM with anal sphincter involvement, the wide excision (WE) and primary sphincteroplasty (PSp) were performed in 6 cases, narrow excision (NE) and PSp in 5 cases, and incomplete excision (IE) in 1 case, and spontaneous regression after a subsequent delivery was registered in 1 case.…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation of this disease and making firm conclusions is not easy because of inconsistent and small series of patients, often casuistic (2, 5,6,8,11,12,13,16,19,22,30,36,39,42,46,48,52). Up to now only one large systemic review (29) was published and two biggest single retrospective studies (57,41) included 81 and 72 patients appropriately.…”
Section: Introductionmentioning
confidence: 99%